Performa Pertumbuhan Tikus Putih (Rattus norvegicus) yang Diberi Ransum Berbagai Taraf Limbah Udang - Muhammad Sayuti Mas’ud; Aminuddin Parakkasi (Jurnal Agripet, 2009)
Growth performance of white rat (Rattus norvegicus) fed by various of shrimp waste levelsABSTRACT. The objectives of this research are to investigate: (1) The effect of shrimp waste levels in experimental diets on feed intake, daily weight gain, and feed convertion (F/G) of white rats; (2) Optimal level of shrimp waste in white rat diets; and (3) The responses of both male and female white rats to shrimp waste levels. 15 male and 15 female white rats were given pellet ration contain shrimp waste for four weeks. The experimental design used in this research is Completely Randomized Design with 2 x 5 factorial arrangement in 3 replications. The A factor was sex (male and female) and the B factor was shrimp waste levels in ration (0% as control. 5%, 10%, 15%, and 20%). The parameters determined are feed intake, weight gain, and feed convertion of white rats. The results indicate that shrimp waste levels in ration was significantly (P0.05) affect the dry matter intake, whereas the effect on weight gain and feed convertion of white rats was highly significant (P0.01). Sex was significantly affect weight gain (P0.05%), however it was not significance (P0.05%) on dry matter intake and feed convertion of white rats. There were no interaction (P0.05%) between shrimp waste levels in ration and sex of white rats. The conclusion of this research that shrimp waste levels in ration of white rats increase dry matter intake and daily weight gain. Whereas, it decreased feed convertion. The optimal level of shrimp waste in the diet for daily weight gain was 19.44%, while optimal feed convertion 16.62%. Male daily weight gain was higher than female.